Healthcare professionals' perceptions on the use of opioid analgesics for the treatment of cancer-related pain in Cyprus: A mixed-method study - Charalambous, Andreas; Zorpas, Marios; Cloconi, Constantina; Kading, Yolanda (My University, 2019)
Objectives: Pain is considered the most common and debilitating symptom reported by patients affected by cancer, and opioids are at the front line for its effective management. However, the appropriate use of opioids can be limited by healthcare professionals' perceptions on opioids. Therefore, the aim of this study was to explore their perceptions on the use of opioids medication. Methods: This was a study of sequential mixed-method design conducted in Cyprus. As part of the quantitative phase of the study, the Barriers to Opioid Analgesic Availability Test questionnaire was completed by 73 physicians randomly selected. In the qualitative phase, 28 healthcare professionals working in primary and secondary healthcare centers participated in two focus groups. They were asked to express their perceptions on the use of opioid analgesics for the treatment of cancer-related pain. Data were analyzed according to Colaizzis' seven-stage phenomenological analysis. Results: The quantitative analysis showed that 69.85% of physicians acknowledge opiophobia as a main barrier to appropriate pain relief but also explicitly for cancer pain which is not adequately managed (45.19%). In terms of opioids availability, physicians stated that moderate to severe problems in opioids availability were mainly caused by their reluctance to prescribe opioids (49.3%) followed by the laws/regulations in place (41.08%). The qualitative analysis yielded the following six main themes: inadequate training of healthcare professionals in the use of opioid analgesics, inadequate patient/caregivers' awareness of opioid analgesics, opiophobia in healthcare professionals, opiophobia of patients/caregivers, poor management of opioid analgesics by healthcare professionals and patients/caregivers, and ineffective pain relief with opioids. Conclusions: The lack of appropriate education is a significant barrier to opioids use in Cyprus. This is compounded by the attitudes and phobias of both healthcare professionals and the general public. In addition, there are barriers to opioid availability and unsatisfactory cancer pain relief.
Keywords: Opioids; Healthcare professionals; Pain management; Perception